Alarming epidemic of rice tungro disease in North-West India - J. SINGH1, S.S. CHEEMA3 and S.S. SOKHI3, A. VARMA1, F.R. NIAZI1, I. DASGUPTA2 (Indian Phytopathology, 2002)
Rice tungro virus (RTV) was detected in diseased rice crops in Gurdaspur and Amritsar districts, Punjab, India between Aug-Sep. 1998.